2019
DOI: 10.3390/nu11071699
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Polyunsaturated Fatty Acids Decrease Long-Term Diabetic Risk of Offspring of Gestational Diabetes Rats by Postponing Shortening of Hepatic Telomeres and Modulating Liver Metabolism

Abstract: The long-term influence of gestational diabetes mellitus (GDM) on offspring and the effect of omega-3 polyunsaturated fatty acids (n-3 PUFA) on GDM offspring are poorly understood. We studied the long-term diabetic risk in GDM offspring and evaluated the effect of n-3 PUFA intervention. Healthy offspring rats were fed standard diet (soybean oil) after weaning. GDM offspring were divided into three groups: GDM offspring (soybean oil), n-3 PUFA adequate offspring (fish oil), and n-3 PUFA deficient offspring (saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 60 publications
2
17
2
Order By: Relevance
“…The protein concentrations were determined through a colorimetric assay. Commercially available kits were used to measure the level of malondialdehyde (MDA) and glutathione (GSH) and the activity of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) according to the manufacturer’s instructions (Nanjing Jiancheng Biotechnology Institute, Nanjing, China) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein concentrations were determined through a colorimetric assay. Commercially available kits were used to measure the level of malondialdehyde (MDA) and glutathione (GSH) and the activity of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) according to the manufacturer’s instructions (Nanjing Jiancheng Biotechnology Institute, Nanjing, China) …”
Section: Methodsmentioning
confidence: 99%
“…The levels of tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, and IL-10 in the pancreas of GDM offspring were determined using commercially available ELISA kits (Nanjing Jiancheng Biotechnology Institute, Nanjing, China) according to the manufacturer’s instructions …”
Section: Methodsmentioning
confidence: 99%
“…GDM is associated with inhibition of glycogen synthesis, affecting the citric acid cycle and gluconeogenesis (Gao et al, 2019b). One study reported that the prevalence of non-alcoholic fatty liver disease among women with a history of GDM was 14-38% higher than in women without such history (Sattari et al, 2020).…”
Section: Ffis Target Hepatic Gluconeogenesis and Glycogen Storagementioning
confidence: 99%
“…During obesity, the excess of lipids in the AT promotes lipotoxicity, leading to liver damage and macrophage infiltration [201,202,221]. Again, the dietary composition of lipids may play an important role in this context, with omega-3 FFAs displaying interesting anti-inflammatory properties [222][223][224]. Along with the KC, these macrophages have been indicated as mediators of hepatic inflammation during obesity.…”
Section: Livermentioning
confidence: 99%